394OKnowledge, attitude and practice of cervical cancer screening and vaccination among female relatives of cancer patients. (24th November 2019) - Mullapally, S K; Gorli, M; Satyavati, V; Digumarti, L; Digumarti, R
Abstract: Background: The various screening methods for include Paps smear, VIA (Visaul inspection with acetic acid), HPV screening etc. Female relatives of any cancer patients are attractive population for screening programmes as they may be receptive to cancer screening awareness initiatives. Methods: Prospective Single institutional study among the female relatives of cancer patients visiting OPDs was done. Questionnaire was given by oncology nurses on the various topics of Knowledge, Attitude and Practice of cervical cancer and screening. 9 questions on personal demographic and social details; 12 questions about knowledge about cervical cancer, screening and HPV vaccination. Attitude assessed by 6 questions with 3 point Likert scale of "Agree, Neutral and Disagree". Barrier in Pap smear, HPV testing and HPV vaccination assessed by 4 options to choose (no idea, harmful, no facility, fear of results). Practice was assessed by asking whether they have undergone Pap smear, HPV testing or if any of the family member has got HPV vaccination. Mean scores were calculated for knowledge section. The attitude was taken favourable if the scores were less than 12(the total if all neutral options are selected by patient). Descriptive statistics was used for analysis with SPSS version 20. Results: 42 female relatives participated in the study. Their median age was 35.5yrs (22-70). Most of them had studied from 6-10 class (38%). Majority were married (80%). Median age of marriage was 20yrs (14-35) and mostly belonged to middle class. The knowledge as assessed using mean knowledge score was 27% (poor <50%). Awareness about cervical cancer, screening and vaccination was 64%, 43%, 24% respectively. The overall attitude towards vaccination was unfavourable (74%). Main barrier in HPV vaccination, Pap smear and HPV testing reported by patient was lack of any idea about the same (90%). Practice of either Pap smear, HPV testing or HPV vaccination was only 10% in this population. Conclusions: There is significant lack of knowledge, attitude and practice for carcinoma screening and vaccination in the female relatives of cancer patients who visited HBCHRC, a tertiary cancer centre in rural India. The lack of knowledge is the main barrier and needs urgent steps to correct it. Legal entity responsible for the study: Homi Bhabha Cancer Hospital and Research Centre, Visakhapatanam. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.